Financial inclusion and their role in renewable energy and non-renewable energy consumption in China: Exploring the transmission channels - Yukun Li; Jian Chen; Muhammad Tayyab Sohail (My University, 2022)
Abstract China is the most polluted economy in the world, facing the challenges of increased CO2 emissions. In this way, energy consumption is a key factor in CO2 emissions. To this end, this study empirically examines the effects of financial inclusion and education on energy consumption employing the ARDL approach for China during the period 1995–2019. The results suggest that financial inclusion has a positive effect on renewable energy consumption, but a negative impact on renewable energy and total energy consumption. The results show that education reduces non-renewable consumption and increases renewable energy consumption in the long-term. Long-run and short-run findings are also consistent and robust in the sensitivity analysis. Based on findings, China should invest in the education sector and increase financial inclusion to reduce energy consumption to meet environmental sustainability.
Keywords: Consumption; Renewable energy credit; Energy, Environment, Economic Growth